A experiência de comércio justo de agricultores familiares da cooperativa COOPFAM de Poço Fundo (MG): identificando os obstáculos e as potencialidades da transição para a agricultura de base ecológica - Cavino, Valquiria de Cássia Oliveira (Universidade Federal de São Carlos, 2012)
The present research proposes to systematize the experience of Fair Trade developed by farmers associated to a cooperative (Coopfam) and understand the obstacles and potentials of the model transition for the ecologically based agriculture. Initilly, a study was conducted with documentary bases and agricultural censos seeking to characterize the situation and the social economic and agri-environment of the municipality. The results of the research allow to understand the local rural landscape, regarding to historical, geographical and agricultural aspects. Then, a group of family farmers from the cooperative was interviewed, orally, where the trajectory of the farmes and the process that led to adherence to fair trade were reconstructed, qualifying these changes, seeking to understand the reasons of the transition and the meaning of this experience, of social cultural or economics terms. Among the main results, it was found that the certification Fair Trade provided improvements in the production field environmentally sustainable. The fair condition of production and commercialization is causing dissatisfaction between the producers who claims that the price received at the present moment is not advantegeous due to the appreciation of the real against the dollar making foreign prices reduce in relation to internal prices, the minimum prices should be reviewed by the importers and by the chain of the fair trade.
The experience of fair trade of family farmers of the cooperative COOPFAM of Poço Fundo (MG): identifying the obstacles and potenteals of transition for the ecologically based agriculture
Keywords: Agroecologia; Comércio justo; Agricultura familiar; Fair trade; Agroecology; Family farming; CIENCIAS AGRARIAS::AGRONOMIA